2022
DOI: 10.3201/eid2807.212586
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Diverse Highly Pathogenic Avian Influenza A(H5N1/H5N8) Viruses among Wild Waterfowl and Domestic Poultry, Japan, 2021

Abstract: H ighly pathogenic avian influenza (HPAI) viruses are known to have zoonotic potential (1). There-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 15 publications
(13 reference statements)
0
37
0
Order By: Relevance
“…In winter 2021–2022, many H5N1 HPAIVs were introduced to the Far East, including Japan, Russia (Sakhalin), and the Republic of Korea [ 11 , 13 ]. Phylogenetic analysis results indicated that three groups of H5 HPAIVs were introduced into Japan, probably by bird migration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In winter 2021–2022, many H5N1 HPAIVs were introduced to the Far East, including Japan, Russia (Sakhalin), and the Republic of Korea [ 11 , 13 ]. Phylogenetic analysis results indicated that three groups of H5 HPAIVs were introduced into Japan, probably by bird migration.…”
Section: Discussionmentioning
confidence: 99%
“…Most H5N1 isolates in northern Japan in Group 1 were genetically close in all eight gene segments to those circulating in Europe and North America in the same season, indicating that these viruses did not cause any genetic reassortment events with local viruses and had the potential to travel for a longer distance, such as from nested lakes in the north to the Far East along the Sea of Okhotsk as well as European countries [ 13 ], and were simultaneously introduced into the Far East, Europe, and North America [ 9 , 25 ]. In parallel, H5 HPAIVs isolated in southern Japan and the Republic of Korea at the end of 2021 were genetically distinct from Group 1 [ 13 ] and formed two different genetic subgroups in the phylogenetic tree of the HA gene (Group 2 and 3). Viruses in Group 3 were genetically close to Asian isolates in 2020–2021 [ 11 , 12 , 13 ], implying that H5 HPAIVs, mainly the H5H8 subtype in Group 3, had been kept in the Far East since the winter of 2020–2021.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The largest number of HPAI outbreaks was reported in Europe until 2022, with H5N1 the most dominant subtype in most countries. In the 2021/2022 season (i.e., from November 2021 to May 2022) in Japan, 25 HPAI outbreaks across 12 prefectures were reported in poultry farms (chickens, ducks, and emus), and 107 cases across 8 prefectures were confirmed in wild birds (e.g., a hooded crane [ 8 ], crows, and eagles [ 9 ]) or the environment [ 10 ]. HPAIV infection was also confirmed in wild mammals (an Ezo red fox and a raccoon dog) in Hokkaido prefecture [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%